2017
DOI: 10.3758/s13423-017-1408-3
|View full text |Cite
|
Sign up to set email alerts
|

The SNARC effect is not a unitary phenomenon

Abstract: Models of the spatial-numerical association of response codes (SNARC) effect-faster responses to small numbers using left effectors, and the converse for large numbers-diverge substantially in localizing the root cause of this effect along the numbers' processing chain. One class of models ascribes the cause of the SNARC effect to the inherently spatial nature of the semantic representation of numerical magnitude. A different class of models ascribes the effect's cause to the processing dynamics taking place d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…Arend, Yuen, Ashkenazi, & Henik, in press) have also noted that observed behavioral results with synesthetes may reflect the influences of both implicit MNL representations and explicit synesthetic NFs. We concur, but go even further: Recent evidence from numerical cognition argue that the MNL is not a unitary phenomenon, but instead reflects both spatial-numerical mental representations and response-selection (Basso Moro, Dell'Acqua, & Cutini, 2018). Given this complexity, we must consider many more possible mappings between numbers and space to fully account for the wide variability in these implicit and explicit measures across both synesthetes and non-synesthetic controls.…”
Section: Theoretical Implicationsmentioning
confidence: 56%
“…Arend, Yuen, Ashkenazi, & Henik, in press) have also noted that observed behavioral results with synesthetes may reflect the influences of both implicit MNL representations and explicit synesthetic NFs. We concur, but go even further: Recent evidence from numerical cognition argue that the MNL is not a unitary phenomenon, but instead reflects both spatial-numerical mental representations and response-selection (Basso Moro, Dell'Acqua, & Cutini, 2018). Given this complexity, we must consider many more possible mappings between numbers and space to fully account for the wide variability in these implicit and explicit measures across both synesthetes and non-synesthetic controls.…”
Section: Theoretical Implicationsmentioning
confidence: 56%
“…It may be argued that the effects in both hands are significant due to the distance effect. Some research indeed found that the numerical distance modulated the SNARC effect (Basso Moro et al, 2018). In order to rule out this possibility, we binned all the magnitudes below and above 5 together (small vs. large), to further test whether there would be no difference between both-hands effects in Experiment 5 and 6, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For example, whereas dominant theories ascribe number, order, and hand (left/right) interactions to purely spatial interactions, an alternative view holds that response-related factors are crucial (Verguts et al, 2005). Relatedly, several studies revealed that spatial associations arise at response-related stages (Basso Moro et al, 2018; Gevers et al, 2010; Gevers, Ratinckx, et al, 2006; Keus et al, 2005; Keus & Schwarz, 2005; Toomarian & Hubbard, 2018a). Fleshing out such proposals will require investigating the individual roles of the two hands in the generation of numerical and order effects.…”
Section: Introductionmentioning
confidence: 98%
“…Such evidence suggests at least some functional flexibility of SNAs, consistent with the view that there is not a single, static MNL. Instead, we argue that SNAs arise from a multitude of cognitive processes and may be reflected in multiple representations (see also Basso Moro et al, 2017). We know that there is the ability to influence the SNARC effect in groups and individuals, but we do not know what the accompanying neural signature of this change would look like.…”
Section: Interactive Specializationmentioning
confidence: 90%